Metabolomics profiles in acute-on-chronic liver failure: Unveiling pathogenesis and predicting progression - Liu, Guofeng; Wang, Xiaoze; Fan, Xiaoli; Luo, Xuefeng (Frontiers in Pharmacology, 2022)
Acute-on-chronic liver failure (ACLF) usually develops based on acute decompensation (AD) of cirrhosis and is characterized by intense systemic inflammation, multiple organ failure, and high short-term mortality. Validated biomarkers for the diagnosis and prognosis of ACLF remain to be clarified. Metabolomics is an emerging method used to measure low-molecular-weight metabolites and is currently frequently implemented to understand pathophysiological processes involved in disease progression, as well as to search for new diagnostic or prognostic biomarkers of various disorders. The characterization of metabolites in ACLF has recently been described via metabolomics. The role of metabolites in the pathogenesis of ACLF deserves further investigation and improvement and could be the basis for the development of new diagnostic and therapeutic strategies. In this review, we focused on the contributions of metabolomics on uncovering metabolic profiles in patients with ACLF, the key metabolic pathways that are involved in the progression of ACLF, and the potential metabolite-associated therapeutic targets for ACLF.